The Influence of Personality, Reputation, Value, and Corporate Identity on Customer Satisfaction at Bank Syariah Mandiri Mataram Branch - Riduan Mas’ud; Khairul Hamim (UIN Sunan Gunung Djati, 2020)
In increasing banking profits, customer satisfaction is something that needs to be taken into account. This study aims to analyze the effect of Reputation, personality, identity, and company value on customer satisfaction at the Bank Syariah Mandiri Mataram Branch. The method used is descriptive quantitative using a Likert scale. Many steps are carried out before performing regression, such as normality and linearity tests. This study found that personality, value reputation, and corporate identity significantly and positively influence customer satisfaction at Bank Syariah Mandiri Mataram Branch. The personality variable is the most dominant in influencing customer satisfaction at Bank Syariah Mandiri Mataram Branch.